MAIS UMA NARRATIVA ANTES DE ACABAR O MUNDO (ENSAIO SOBRE O TEMA DA VIAGEM EM MURILO RUBIÃO) - Bastos, Hermenegildo José (Organon, 2003)
In murileon’s fiction geography, the mountain is opposed tothe sea. The characteres are former sailors or sailors descendents. Thenostalgia for the sea relates to the action and bravery of the past. In thenarrative’s present, they dwell in country little towns. They move to the bigcities or they wait for its representatives to come and civilize them. Thetrain was substituted for the ship, each one representing one step in capitalismhistory: the Iberian and British expansion. The narration of thecolonial adventure takes place. The fantastic writing reveals the ghosts ofthe modernity adventure, who wander between past and present. The mostremote layers of the memory of this adventure are the ones of the littletowns, and the most recent, the ones of the big cities. Different ways ofproduction are confronted with different ways of survival. The narrator’sbad faith denounces his complicity in power games.